E-Module Validity with Approach SETS (Science, Environment, Technology, and Society) Integrated Characters in Measurement Materials for High School Physics Learning - Sherly, Sherly; Desnita, Desnita (PILLAR OF PHYSICS EDUCATION, 2023)
Character education is a special concern for national education goals. As a result of the nation's character, which has become ingrained in the ideals of the Indonesian nation's personality, being lost in schooling at this time. Learning closely relevant to daily issues might help develop good character. The minister of education in particular has announced the government's autonomous learning curriculum. The autonomous curriculum is an extracurricular study-based competency-based program designed to improve students' soft skills and character. As a consequence, it requires adjustments to processes, media, and sources or teaching materials. Measurement materials for learning physics in high school have been developed using a method called character-integrated SETS. In order to produce teaching materials that suit the needs, a number of tests are needed. One of the tests carried out is the validity test. This article presents the results of the expert validity test on the developed e-module. This research is a development research using the 4D model (Four-D model), which is limited to three stages, namely define, design, and develop. The research subjects consisted of 3 lecturer validators from the Physics Department of Faculty of Mathematics and Natural Sciences Padang State Univercity. Validity is viewed from the components of material substance, visual communication display, learning design, software use, SETS (science, Environment, Technology and Society) approach components, and character assessment. Data validation results were analyzed using Aiken's V formula. The average value of e-module validation is 0.85 with a valid category so that e-modules are produced which are valid